Claudio Moraga: A Passion for Multi-Valued Logic and Soft Computing - Seising, Rudolf; Allende-Cid, Héctor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book is an authoritative collection of contributions by leading experts on the topics of fuzzy logic, multi-valued logic and neural network. Originally written as an homage to Claudio Moraga, seen by his colleagues as an example of concentration, discipline and passion for science, the book also represents a timely reference guide for advance students and researchers in the field of soft computing, and multiple-valued logic. .
From the Content: From Multi-valued Logics to Fuzzy Logic -- A Dialogue Concerning Contradiction And Reasoning -- Some Entertainments Dealing with Three Valued Logic -- Fuzziness as an Experimental Science: an Homage to Claudio Moraga -- Some reflections on the use of interval fuzzy sets for dealing with Fuzzy Deformable Prototypes -- The way to the BliZ.
Keywords: Algorithms; Electronic circuits; Artificial intelligence; Algorithms; Electronic Circuits and Systems; Artificial Intelligence